AB1099 CHAGAS DISEASE REACTIVATION IN THE RHEUMATOLOGIC IMMUNOSUPPRESSED PATIENT. IS IT NO LONGER AN ORPHAN DISEASE?. (June 2019) - Ringer, Ariana; Ruffino, Juan Pablo; Cuadranti, Nadia; Martinez, Florencia; Argento, Cecilia; Rolla, Ignacio; Vandale, Juan Manuel; Achilli, Carla; Palatnik, Mariano; Cortese, Noel; Lagrutta, Mariana; Leiva, Rodolfo; et al.
Abstract : Background: Chagas disease (CD) is an endemic and neglected infection in Latin America. Due to international human migration, it has become a worldwide issue. Scarce evidence is published regarding its behavior in rheumatic diseases (RD) with rheumatologic treatments (RT). Objectives: To screen and follow up patients with CD under RT. To detect clinical and serological reactivation. Methods: A systematic screening was conducted between January 2018 and January 2019 in a third-level Hospital in Argentina. Patients with CD and concomitant RD under RT were included. Assessments were done before and after RT. A direct (Strout) and indirect method (Polymerase chain reaction-PCR) were performed in order to detect parasitemia, levels of antibodies were evaluated by three techniques. Clinical, infectological and cardiological features were examined. Everything was assessed in, at least, two opportunities, separated by a minimum of one month. If treatment was modified or clinical condition changed, all the evaluations were repeated as before. In case of reactivation, specific treatment was indicated and follow up controls were stricter. Results: 38 patients were identified. RD: Rheumatoid Arthritis: 22 (57, 9%), Systemic lupus erythematosus: 4 (10, 5%), Systemic Sclerosis: 3 (7, 9%), Vasculitis: 2 (5, 3%), Psoriatic Arthritis: 1 (2, 6%), others: 6 (15, 8%). RT: classic, synthetic and biological disease-modifying antirheumatic drugs, cyclophosphamide and corticosteroids. Two reactivations were detected with both direct and indirect methods, with a significant title antibody increment and consistent clinical signs and symptoms. Cardiological abnormalities were found. A 64-years old lady with Microscopic Polyangiitis, under prednisone 60 mg/day and a 57-years old lady with Systemic Lupus Erythematosus under hydroxychloroquine and prednisone 40 mg/day, who happen to be sisters. They did not have other treatments. Both of them developed high fever, myalgias, arthralgias and asthenia. Other infections were ruled out. They received Benznidazole and Nifurtimox respectively. After one-week treatment, Strout and PCR became negative and antibodies decreased, with remarkable clinical improvement. Conclusion: Two patients with parasitemia and concomitant symptoms were detected, after high doses of corticosteroids. Because they were sisters, a genetic background would also play a role. Parasite's screening before starting immunosuppression and its follow-up during treatment in search of reactivation should be integrated to rheumatology daily practice in endemic countries. It should also be taken into account in patients from non-endemic countries that have an epidemiological nexus. CD specific antibodies determination, Strout and PCR are economic and practical techniques, although they require qualified personnel and equipment. In areas with high prevalence of CD, the benefits of this measures would outweigh costs. A more advanced study should be performed to extend our knowledge. Disclosure of Interests: None declared